(untitled) (African Journal of Law and Politics, 2023)
The enactment of the criminal procedure code and its publication in the official gazette of Cameroon on October 18, 2005, raised the hopes of actors in the criminal justice system. This led many to believe that unlike in the past the protection of individual freedoms is now the rule rather than the exception. By this action, the Cameroonian legislator acknowledges the thoughts of LEON BLUM who stated that: "any society which claims to ensure freedom for men, must begin by guaranteeing them existence". To underscore the importance of individual freedoms, an entire chapter of the Code was dedicated to the mechanisms for the compensation of victims of illegal detention. At first view, it may be tempting to express satisfaction for the availability of instruments for redress to victims of illegal detention and related abuses. However, close examination of the conditions and modalities for obtaining the statutory compensation raises a lot of questions about the true intentions of the legislator. The issues at stake includes; the gravity of the damage sustained, the use of ambiguous language, the fact that proceedings are held behind closed doors, the exclusion of the heirs and assigns of victims from due compensation, as well as blatant neglect of fines levied against a member-state by an international organ, constitute grounds for urgent reform of the system of compensation.